Clinicopathological analysis of sclerosing angiomatoid nodular transformation in the spleen - Shufei Wei; Yongliang Han; Yingyong Hou; Liangliang Wang (Wolters Kluwer Medknow Publications, 2024)
Background: Splenic sclerosing angiomatoid nodular transformation (SANT) is a rare benign nodular lesion in the red medulla of the spleen. In the past, SANT has not been consistently recognized as the name for this condition and was often misdiagnosed for other conditions. In recent years, SANT has been acknowledged by most scholars as multiple reports have been published. Aim: To assess the clinicopathological features of SANT to identify the histological characteristics of SANT to improve diagnosis and clinical treatment. Materials and Methods: We assessed 25 cases of SANT diagnosed at Zhongshan Hospital affiliated with Fudan University from September 2014 to October 2021, including 14 men and 11 women, aged 24-62 years old. Results: Fourteen cases were complicated with benign tumors of the liver, pancreas, kidney, uterus, and prostate. One case was complicated with renal clear cell carcinoma, and one was complicated with hepatocellular carcinoma. The gross neoplasm is multinodular and well defined. Histologically, angiomatoid nodules are composed of fattened, round, or irregular blood vessels, with or without red blood cells in the lumen, with unequal red blood cell extravasation, and fibrocytes around the nodules. The hemangiomatous nodules were positive for CD31 and CD34, while the vascular wall smooth muscle cells and fibrocytes around the nodules were positive for SMA. Conclusion: The diagnosis of SANT requires a combination of immunohistochemical and histological features, and early splenectomy is crucial for treatment.